2022
DOI: 10.3390/jof8020130
|View full text |Cite
|
Sign up to set email alerts
|

Serological Changes in Anti-Aspergillus IgG Antibody and Development of Chronic Pulmonary Aspergillosis in Patients Treated for Pulmonary Tuberculosis

Abstract: Chronic pulmonary aspergillosis (CPA) is an important infection to understand in survivors of pulmonary tuberculosis (PTB). However, limited data are available regarding CPA development and its predisposing factors following PTB. We investigated the development of, and the predisposing factors for, CPA following the completion of PTB treatment. A total of 345 patients, with newly diagnosed culture-positive PTB (between January 2015 and December 2018), were included. Enrolled cases were categorized into four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
(56 reference statements)
1
19
0
Order By: Relevance
“…Anti- Aspergillus IgG antibody is also not specific for CPA. Detectable antibodies are also found in those recovering from invasive aspergillosis, chronic invasive Aspergillus rhinosinusitis or granulomatous sinusitis, allergic bronchopulmonary aspergillosis, and Aspergillus bronchitis (usually seen in those with bronchiectasis), as well as some healthy people ( Kim et al., 2022 ). In healthy populations, Aspergillus IgG was detectable in one of 222 (0.5%) in France ( Guitard et al., 2012 ), 11 of 90 (12%) in Indonesia ( Setianingrum et al., 2020 ), six of 42 (14%) in Belgium ( Van Hoeyveld et al., 2006 ), and four of 150 (2.7%) in the UK ( Wilopo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti- Aspergillus IgG antibody is also not specific for CPA. Detectable antibodies are also found in those recovering from invasive aspergillosis, chronic invasive Aspergillus rhinosinusitis or granulomatous sinusitis, allergic bronchopulmonary aspergillosis, and Aspergillus bronchitis (usually seen in those with bronchiectasis), as well as some healthy people ( Kim et al., 2022 ). In healthy populations, Aspergillus IgG was detectable in one of 222 (0.5%) in France ( Guitard et al., 2012 ), 11 of 90 (12%) in Indonesia ( Setianingrum et al., 2020 ), six of 42 (14%) in Belgium ( Van Hoeyveld et al., 2006 ), and four of 150 (2.7%) in the UK ( Wilopo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPA, usually with an aspergilloma, was found in 8.3% of 350 previously treated PTB patients who were subsequently hospitalized in Rio de Janeiro, Brazil over an unclear time frame ( Ferreira-Da-Cruz et al., 1988 ). A prospective study in Seoul, South Korea found 3% of culture-proven PTB cases to have CPA in the 2 years after completion of ATT ( Kim et al., 2022 ). For consistency, our study used 1.5% annually, and modeled the overall 5-year-period prevalence of CPA after TB using 7.5%.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter study, there was higher resolution rate of primary cavity after TB treatment in the 'seroconversion' group (40%) and 'persistently seronegative' group (75.9%) as compared to 'seroreversion' group (0%) and 'persistently seropositive' group (22.7%). 9 In our study 5/8 patients (~63%. 95% CI: 24.5-94.5) who had 'self-resolving CPA" had resolution of their consolidation (without development of new cavity) at the end-of-therapy as compared to their baseline chest images.…”
Section: Discussionmentioning
confidence: 43%
“…Recently, Page et al [61] found a CPA incidence of 6.5% in Ugandan PTLD patients on a resurvey after 2 years. Kim et al [62] reported a CPA incidence of 2.9% during a 2-year follow-up in individuals with PTLD. Interestingly, patients with active PTB also have a higher occurrence of A. fumigatus coinfection.…”
Section: Chronic Pulmonary Aspergillosismentioning
confidence: 99%